2016
DOI: 10.3390/molecules21111593
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Alkane Oxidation with meta-Chloroperoxybenzoic Acid (MCPBA) Catalyzed by Organometallic Cobalt Complexes

Abstract: Cobalt pi-complexes, previously described in the literature and specially synthesized and characterized in this work, were used as catalysts in homogeneous oxidation of organic compounds with peroxides. These complexes contain pi-butadienyl and pi-cyclopentadienyl ligands: [(tetramethylcyclobutadiene (10). Complexes 1 and 2 catalyze very efficient and stereoselective oxygenation of tertiary C-H bonds in isomeric dimethylcyclohexanes with MCBA: cyclohexanols are produced in 39 and 53% yields and with the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…It is important to note that catalyzed by 2 oxidation of cis-1,2-dimethylcyclohexane with meta-CPBA occurs stereoselectively (the trans/cis ratio was 0.3; (we found previously analogous effect; see, for example, ref. [108]).…”
Section: Hydroperoxidation Of Alkanes With H 2 Omentioning
confidence: 99%
“…It is important to note that catalyzed by 2 oxidation of cis-1,2-dimethylcyclohexane with meta-CPBA occurs stereoselectively (the trans/cis ratio was 0.3; (we found previously analogous effect; see, for example, ref. [108]).…”
Section: Hydroperoxidation Of Alkanes With H 2 Omentioning
confidence: 99%
“…To date, some cobalt compounds, including Tp R [ 27 , 28 ] and To M [ 10 ] complexes, have been employed as catalysts for hydrocarbon oxygenation with organic peroxides (ROOH) such as tert -butyl hydroperoxide (TBHP) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and meta -chloroperbenzoic acid ( m CPBA) [ 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Therefore, we explored catalysis of the entitled mixed ligand complexes toward alkene oxidation with TBHP and alkane oxidation with m CPBA as indicated below.…”
Section: Resultsmentioning
confidence: 99%
“…These trends suggested that the reactions proceeded through a radical mechanism. It is known that oxidations of aliphatic C–H groups with H 2 O 2 through radical mechanisms result in generation of the corresponding alkylhydroperoxides, and the resulting alkylhydroperoxides are converted to alcohols when the reaction mixtures are treated with PPh 3 quencher prior to analysis [ 43 ]. In our system, the absence of an increase of A suggested that cyclohexenylhydroperoxide did not form.…”
Section: Resultsmentioning
confidence: 99%
“…When using H 2 O 2 as oxidant, a higher selectivity towards the alcohol is observed, while with TBHP, the amount of this product is lower than that of the ketone ( [13][14][15][16].…”
Section: Conventional Mediummentioning
confidence: 99%